Public finance as a component of the financial system - Shainoha, A. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2021)
The article focuses on the analysis of the dynamics and current state of development of public finances in Ukraine. Theoretical aspects of the public finance system are considered, namely: their essence, functions and structure, as well as the modern public finance system of Ukraine, its structure and components. Public finance is a key component of Ukraine's financial system, which owns more than half of all financial resources and includes various financial institutions that perform state functions. The multifunctionality of public finances determines their extensive structure, the main component of which is the State Budget. The implementation of the State Budget of Ukraine for nine years (2013-2021) as a key component of public finances was analyzed. The analysis of the revenue and expenditure part of the State Budget of Ukraine for four years (2018-2021) was conducted, and the shortcomings of the formation and use of budget funds were identified.The study identified the main problems and shortcomings of the public finance system of Ukraine, where the central place is occupied by problems with the formation and use of budget funds and inefficient functioning, resulting in persistent budget deficits, rising debt burden and tax pressure on the population. To eliminate the budget deficit, it is necessary to reduce the number of expenditure items and conduct careful control over expenditures. This paper has developed proposals to improve the state and efficiency of the public finance system, eliminate existing problems of revising and reducing the share of expenditures, increase revenue through non-tax revenues and give autonomy to local governments, which will reduce excessive centralization of the budget system and improve financial position of the state.